Opportunities and challenges of natural killer cell-derived extracellular vesicles - Qi, Yuchen; Zhao, Xiang; Dong, Yan; Wang, Min; Wang, Junyi; Fan, Zhichao; Weng, Qin; Yu, Hua; Li, Jianjun (Frontiers in Bioengineering and Biotechnology, 2023)
Extracellular vesicles (EVs) are increasingly recognized as important intermediaries of intercellular communication. They have significant roles in many physiological and pathological processes and show great promise as novel biomarkers of disease, therapeutic agents, and drug delivery tools. Existing studies have shown that natural killer cell-derived EVs (NEVs) can directly kill tumor cells and participate in the crosstalk of immune cells in the tumor microenvironment. NEVs own identical cytotoxic proteins, cytotoxic receptors, and cytokines as NK cells, which is the biological basis for their application in antitumor therapy. The nanoscale size and natural targeting property of NEVs enable precisely killing tumor cells. Moreover, endowing NEVs with a variety of fascinating capabilities via common engineering strategies has become a crucial direction for future research. Thus, here we provide a brief overview of the characteristics and physiological functions of the various types of NEVs, focusing on their production, isolation, functional characterization, and engineering strategies for their promising application as a cell-free modality for tumor immunotherapy.